KEDUDUKAN HUKUM HAK MILIK DAN FUNGSI SOSIAL HAK ATAS TANAH - Ferliansyah Ilham Akbar (Sekolah Tinggi Pariwisata Mataram, 2022)
This exploration is a regulating legitimate examination. Article 6 of Regulation Number 5 of 1960 concerning Fundamental Guidelines on Agrarian Standards expresses that all land freedoms have a social capability. The social capability of land freedoms is that all land privileges that exist in an individual can't be utilized exclusively for his own advantages however the land should likewise give advantages to the interests of the local area and the state. Then again, the guideline in Article 20 expresses that property freedoms are genetic, most grounded, and fullest privileges that individuals can have ashore, remembering that land freedoms have social capabilities. This study will examine how the lawful place of property privileges to land and the social capability of land freedoms is and will break down how the legitimate assurance of land freedoms is in the social capability of land privileges. With the goal that the creator will figure out how the position and legitimate assurance of land in the social capability of the material regulations and guidelines.